2012
DOI: 10.1080/15287394.2012.709412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Prototype Point-of-care Instrument Based on Monochromatic X-Ray Fluorescence Spectrometry: Potential for Monitoring Trace Element Status of Subjects with Neurodegenerative Disease

Abstract: Assessment of trace elements such as Cu, Zn, and Se in patients with neurodegenerative disease, such as Alzheimer's (AD) and Parkinson's disease (PD), may be useful in etiologic studies and in assessing the risk of developing these conditions. A prototype point-of-care (POC) instrument based on monochromatic x-ray fluorescence (M-XRF) was assembled and evaluated for the determination of Cu, Zn, and Se in whole blood, plasma, and urine. The prototype instrument was validated using certified reference materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Low plasma selenium concentrations are associated with subtle neurological impairments reflected in soft neurological signs [84,85]. Plasma Se was the only statistically significant difference of up to 16 elements identified for PD patients [86] relative to Alzheimer's disease patients. Redox-active role is evidenced by an increased lipid peroxidation and reduced glutathione levels [87] and high concentration of iron and free radical generation via autocatalytic mechanisms within neuromelanincontaining catecholaminergic neurons in the substantia nigra.…”
Section: Parkinson's Diseasementioning
confidence: 94%
“…Low plasma selenium concentrations are associated with subtle neurological impairments reflected in soft neurological signs [84,85]. Plasma Se was the only statistically significant difference of up to 16 elements identified for PD patients [86] relative to Alzheimer's disease patients. Redox-active role is evidenced by an increased lipid peroxidation and reduced glutathione levels [87] and high concentration of iron and free radical generation via autocatalytic mechanisms within neuromelanincontaining catecholaminergic neurons in the substantia nigra.…”
Section: Parkinson's Diseasementioning
confidence: 94%
“…Sixty-nine full-text articles were assessed for eligibility. We excluded from the original 69 one study that did not report SD [38], one that reported a geometrical mean [39], and two that did not report the absolute value of Cu levels [10,40]. We also excluded the study by Alimonti et al [41] because the data partially overlapped with some shown in a paper by Bocca and colleagues [42].…”
Section: Meta-analysismentioning
confidence: 99%
“…149,150 Conventional optical uorescence, however, exhibits several limitations as a POC diagnostic strategy due to the lack of portability, high cost, requirement of a specic prociency from the expert, and unsuitability in ambulatory environment. 150 To addresses these issues, a great effort has been made to develop a compact, portable, multiplexed, and cost-effective uorescent modalities [151][152][153][154][155][156] such as smartphone embedment, 157 uorescent lateral ow assay 158 etc.…”
Section: In Vitro Biosensing Systemmentioning
confidence: 99%